2023
DOI: 10.1039/d3en00014a
|View full text |Cite
|
Sign up to set email alerts
|

Nanomaterials in plant management: functions, mechanisms and prospects

Xing Lv,
Haodong Sha,
Zi Ye
et al.

Abstract: Efficient, sustainable agricultural methods are critical to meet the food requirements of a rapidly growing global population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 207 publications
0
5
0
Order By: Relevance
“…The counterpart fertilizer treatments (ION) were increased by 13% (from 4.2 ± 0.4 to 4.7 ± 0.26) (Figure 3d). Those results show the possibility that nanoparticles can stimulate the expression of plant-related genes [10]. For instance, the application of chitosan nanoparticles on wheat induces the expression of auxin-related genes, expedites the biosynthesis and transportation of indoleacetic acid (IAA), and elevates IAA concentrations in wheat tissues, thereby exerting a positive impact on plant growth [39].…”
Section: Increased Yield Of Wheat Grain Upon Mnfe 2 O 4 Np Exposurementioning
confidence: 96%
See 1 more Smart Citation
“…The counterpart fertilizer treatments (ION) were increased by 13% (from 4.2 ± 0.4 to 4.7 ± 0.26) (Figure 3d). Those results show the possibility that nanoparticles can stimulate the expression of plant-related genes [10]. For instance, the application of chitosan nanoparticles on wheat induces the expression of auxin-related genes, expedites the biosynthesis and transportation of indoleacetic acid (IAA), and elevates IAA concentrations in wheat tissues, thereby exerting a positive impact on plant growth [39].…”
Section: Increased Yield Of Wheat Grain Upon Mnfe 2 O 4 Np Exposurementioning
confidence: 96%
“…Therefore, researchers focus on enhancing plant nutrient uptake efficiency by refining the chemical fertilizers. Recently, studies have shown that under equivalent ionic concentrations, nano-fertilizers composed of macronutrients or micronutrients exhibit higher efficiency than traditional fertilizers and demonstrate the effective reduction of nutrient leaching [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Specialized research providing insights into these inquiries will facilitate the development of innovative nanomaterials with controlled physicochemical properties to support the agricultural management strategies. 264 However, despite the attention given to the prospective benefits of nanomaterials in plant management, there remain numerous obstacles that must be surmounted to fully exploit the capabilities of nanomaterials-enabled technologies for plants. For example, nanomaterials effect on plants majorly depends on exposed concentration and it may cause adverse effects if exceeded beyond a certain limit.…”
Section: Outlook and Concluding Remarksmentioning
confidence: 99%
“…Specialized research providing insights into these inquiries will facilitate the development of innovative nanomaterials with controlled physicochemical properties to support the agricultural management strategies. 264…”
Section: Outlook and Concluding Remarksmentioning
confidence: 99%
“…[35][36][37][38][39][40] These include their ability to interact with DNA, providing protection against mechanical and enzymatic shearing, as well as facilitating the transfer of macromolecules into intact plant cells. [41][42][43][44] There have been limited accounts regarding the application of nanocarriers in sonication-mediated DNA delivery into protoplasts and intact plant cells, reported across various plant species. 12,17,18,42,45 These approaches offer advantages such as cost-effectiveness, species independence, and simplicity.…”
Section: Ultrasonic Treatment Effect On Plant Cell Viabilitymentioning
confidence: 99%